Effect of a primary health care program in Mexican patients with chronic non-communicable diseases - Domínguez López, Arturo Alejandro (2020)
Noncommunicable Chronic Diseases (CNCD) are long-term conditions and their evolution is slow. Currently the number of cases is on the rise and represent the leading cause of death worldwide. The treatments are usually complex and if the population does not begin to take responsibility, taking into account the healthy habits, the consequences will be greater for the health systems. For this reason, a program based on the Primary Health Care approach was prepared, submitted to expert analysis and a pretest-posttest design research was established in the municipalities located in the Toluca Valley, in the center of the country with 188 patients with CNCD.